Synergistic effect of fenugreek-zinc oxide nanoparticles for managing diabetes mellitus in experimental animals - Abdel Fatah, Hala S.; El-Badry, Mohamed A.; Alsubaie, Abdullah; El-Badry, Yaser A. (Penerbit Universiti Kebangsaan Malaysia, 2025)
Fenugreek extract and zinc oxide nanoparticles were prepared using ultrasonication and chemical methods, respectively. The physico-chemical characterization of fenugreek extract and zinc oxide nanoparticles was performed using FT-IR and UV spectroscopy. The phase formation, morphology, and size of particles were investigated by scanning electron microscope and X-ray diffraction. The antidiabetic activities of both Fenugreek extract and zinc oxide nanoparticles were performed using the inhibition assays of α-glucosidase and α-amylase. A mixture of fenugreek and ZnO nanoparticles was prepared under a chemical food strategy and then its efficacy has been examined in preclinical studies on experimental animals. As projected, the fenugreek extract and zinc oxide nanoparticles exerted remarkable antidiabetic activities. It was concluded that they possess a concentration-dependent reduction in the % of inhibition for the α-glucosidase and α-amylase activities. Oral administration of fenugreek extract, zinc oxide nanoparticles, and a mixture of both for 45 days in streptozotocin-prompted diabetic rats exerted a hypoglycemic impact. An expressive reduction in biochemical parameters has been realized with a non-toxic nature of the fenugreek extract, zinc oxide nanoparticles, and the mixture. Conclusively, the superior scope of the nano-mixture for excellent hyperglycemic improvement in contrast to fenugreek extract or zinc oxide nanoparticles supplementation was illuminated via its synergistic effect on diabetic persistence.